Effects of Magnetic Particles Entrance Arrangements on Mixing Efficiency of a Magnetic Bead Micromixer - Kamali, Reza; Shekoohi, Seyed Alireza; Binesh, Alireza (Nano-Micro Letters, 2014)
In this study, a computer code is developed to numerically investigate a magnetic bead micromixer under different conditions. The micromixer consists of a microchannel and numerous micro magnetic particles which enter the micromixer by fluid flows and are actuated by an alternating magnetic field normal to the main flow. An important feature of micromixer which is not considered before by researchers is the particle entrance arrangement into the micromixer. This parameter could effectively affect the micromixer efficiency. There are two general micro magnetic particle entrance arrangements in magnetic bead micromixers: determined position entrance and random position entrance. In the case of determined position entrances, micro magnetic particles enter the micromixer at specific positions of entrance cross section. However, in a random position entrance, particles enter the microchannel with no order. In this study mixing efficiencies of identical magnetic bead micromixers which only differ in particle entrance arrangement are numerically investigated and compared. The results reported in this paper illustrate that the prepared computer code can be one of the most powerful and beneficial tools for the magnetic bead micromixer performance analysis. In addition, the results show that some features of the magnetic bead micromixer are strongly affected by the entrance arrangement of the particles.